ANALISIS DAMPAK KEBIJAKAN PEMBATASAN UANG MUKA KREDIT (DOWN PAYMENT) TERHADAP PERMINTAAN MOBIL DI KOTA MEDAN - Anna Octora Marpaung; Rahmad Syumanjaya (Ekonomi dan Keuangan, 2013)
Transportation is an activity processing to remove things and peoples from one place to another place. One of the tools that can facilitate human transportation in the process is car. Car is one form of land transportation in interest by the public. Various facilities provided by the company in terms of providing car loans cause an increase in the level of consumption occurs in the bubble economy in public life in Indonesia especially in Medan therefore BI have to make a program by issuing a policy for housing credit and minimum down to payment for motor vehicles credit.This research aims to examine effect of the minimum down payment loan policy to sales volume of cars in Medan, both the advantages and disadvantages of economic growth in Medan. This study used descriptive qualitative research methods. The data collection used a documentary study with data analysis techniques through the stages of information collection, reduction, presentation and drawing conclusions. The results of this study concluded that the regulatory scheme LTV tightening by the central bank will have a significant impact in economic growth in Indonesia. Beneficial impact is the rising of credit quality and the expected transition to productive credit so as to grow the economy. Adverse impact especially in the automotive industry is the feared decline in auto sales which lower economic growth in Medan.Keywords : BI's regulations, bubbles economic, the policy, impact.